Geomorfologia e Potencial de Preservação dos Campos de Dunas Transgressivos de Cidreira e Itapeva, Litoral Norte do Rio Grande do Sul, Brasil - TOMAZELLI, LUIZ JOSÉ; DILLENBURG, SÉRGIO REBELLO; BARBOZA, EDUARDO GUIMARÃES; ROSA, MARIA LUIZA CORREA DA CAMARA (Pesquisas em Geociências, 2008)
The association of several favorable factors (high supply of fine sand to the beach, appropriate wind regime, lowland topography) has resulted in the development of a wide transgressive dunefield that stands out as a fundamental element in the coastal landscape of Rio Grande do Sul, southern Brazil. Along the northern littoral of the state, most of this original ecosystem has been destroyed or highly modified in the last decades, mainly due to the intense urbanization that has been settled in the area. However, some remaining segments of the original eolian field can still be found and, due to ecological, cultural and scenic importance its preservation should be a priority. This work identifies the two most significant of these residual eolian fields in the studied area (Cidreira and Itapeva dunefields), discusses their basic characteristics and analyzes the favorable factors for their preservation. In the Cidreira dunefield de main factor for preservation is the occurrence of some corridors that actively feed the dunes with new sand coming from the beach. In the Itapeva dunefield the basic factor is the existence of bimodal winds from nearly opposite directions that creates reversing dunes. To assure the preservation of these important ecosystems for the future generations it is necessary to impede the progress of the urbanization that threatens both dunefields.